Computational Modelling of Tectona Grandis for Economic Investment Decision - Gunawan, Indra; Utama, Ditdit Nugeraha (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Teak trees (Tectona grandis) are well-known for their quality and benefits, and they are in high demand among people worldwide. The high demand for teak trees raises the price of teak trees and creates opportunities to invest in teak trees. This research aims to develop a computational model of teak trees developed using the Functional-Structural Plant Modeling (FSPM) method and Growth-grammar interactive modelling platform (GroIMP) software to visualize teak tree growth over a 20-year period. The model not only considers morphological aspects such as stem height, stem diameter, and leaf size, but also important economic factors for investment decision-making. The simulated teak tree model grows up to 1000 trees in 1 hectare of land with an average selling price of IDR 1,032,500 per tree. Investment metrics such as Break-Even Point (BEP) and Return On Investment (ROI) are used in this study to assess the profitability of teak tree investments. With a minimum total cost of IDR 183,470,000 for 20 years, the model indicates that the BEP is achieved when planting 128 trees. Furthermore, by planting 1000 trees, the ROI can reach a remarkable 462.76% of the total investment cost.